Preliminary study on the separation of Technetium from acidic wastewater using NTAamide (C8) extractant - LIU Zhanyuan; WANG Junli; SHEN Zhen; LUO Fangxiang; YAN Taihong; ZHENG Weifang; WANG Hui (He jishu)
BackgroundThe presence of technetium in spent nuclear fuel reprocessing waste solution significantly increases the pressure of glass solidification and geological disposal of radioactive waste, and poses long-term potential radioactive hazards to the ecosystem. Therefore, it is necessary to separate and extract it in advance.PurposeThis study aims to propose a process for the extraction and purification of technetium that can be well adapted to the plutonium uranium recovery by extraction (PUREX) process, providing support for engineering applications.MethodsBased on the experimental data pertaining to the extraction and separation of technetium utilizing NTAamide(C8), a refined technetium separation process route containing technetium extraction and stripping with ammonium carbonate was meticulously designed whilst impurity ions were washed by oxalic acid mixed with nitric acid. Subsequently, validation of optimized process route was finalized through a series of cascade experiments with several stages' extraction and washing.ResultsExperimental results show that good washing effect on each impurity ion is achieved when the concentrations of oxalic acid and nitric acid are 0.10 mol·L-1. An exceptional technetium recovery rate of 99.9% is attained after 8-stage extraction and 8-stage washing process while the purification factors of strontium, cesium, zirconium, and ruthenium reach 6.9×103, 7.9×104, 4.3×102 and 45, separately.ConclusionThis optimized process proposed in this study provides technical support for the separation and extraction of technetium in post-treatment plants.